Orithopsid crabs from the Lower Cretaceous Paja Formation in Boyacá (Colombia), and the earliest record of parasitic isopod traces in Raninoida. (December 2020) - Luque, Javier; Cortés, Dirley; Rodriguez-Abaunza, Alejandra; Cárdenas, Diana; de Dios Parra, Juan
Abstract: The Barremian–Aptian Paja Formation, as exposed in Villa de Leyva and nearby areas (Boyacá, Colombia), is one of the most fossiliferous Cretaceous units in northern South America, yet no fossil crabs had ever been recorded from this formation in the region. Here we report the first occurrence of crabs from the upper Aptian "Arcillolitas con nódulos huecos" Member of the Paja Formation in Boyacá, belonging to two species of orithopsid crabs: Bellcarcinus aptiensis Luque, 2014 and Planocarcinus olssoni (Rathbun, 1937 ). The newly collected material — represented by dozens of samples in small nodules — includes individuals preserving key rostral, orbital and pereonal traits previously unknown from the type material. Furthermore, a few specimens of B. aptiensis have swellings in their branchial regions, consistent with the deformation produced by parasitic isopods infesting the crab's gill chambers. To our knowledge, this is the first record of parasitic isopod traces in the family Orithopsidae, and the oldest evidence of isopod parasitism in raninoidan crabs. The new material here reported increases the number or marine arthropods known from the fossiliferous Paja Formation in Boyacá and provides valuable information for further palaeoecological reconstructions of these shallow-marine settings in northern South America during the Early Cretaceous.